(untitled) (Revista Direito em Debate, 2023)
This article focused on the criminal viability of polyfamily family entities in the face of the non-characterization of the crime of bigamy and from the perspective of deconstructing monogamy as a legal principle. In other words, the aim was to discuss that there is no obstacle to the effective legal recognition of such formats in the criminal field, highlighting the criminal feasibility, including that of marriage involving such entities. It started from the hypothesis that Brazilian Law, guided by the principle of affectivity in Family Law, does not impose any obstacle to the acceptance of the modality of family living in polyamory, notably in relation to the criminal scope. Pierre Bourdieu’s theory of Symbolic Power guided the analysis of the proposed object and problematic and allowed the understanding of the relationships between Power and Law, revealing to what extent the legal phenomenon imposes a system of power (control) over human bodies through conditioning of the relational identities adopted by individuals in society. The objective was to analyze the problem that revolves around the need for full legal recognition for family entities that are based on polyamory, especially with regard to criminal aspects. Taking as a paradigm the notion of deconstructing monogamy as a principle of the legal system. An exploratory and qualitative methodology was adopted, using a bibliographic review and the use of secondary data.